2006
DOI: 10.1002/gps.1714
|View full text |Cite
|
Sign up to set email alerts
|

Clinically significant non‐major depression in a community‐dwelling elderly population: epidemiological findings

Abstract: CSNMD is common among community-dwelling elders in Taiwan, and with its identical demographic characteristics, but qualitatively different presentation, we suggest CSNMD may be considered part of a spectrum of severe late life depressions with a distinct manifestation. Major depression and CSNMD may share common demographic characteristics with different manifestation. We conclude that late-life depression is a dimensional disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
1
10

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 35 publications
3
18
1
10
Order By: Relevance
“…The 17.8% rate of reported suicidal thinking during a monthly period found in this sample of elderly aboriginal women might be considered relatively high. Compared to a study of non-aboriginal elderly women in Taiwan, which found a 13.5% one-month prevalence rate of suicidal thinking (Chen et al, 2007), our results show elderly aboriginal women report a higher frequency of suicidal ideation. Lower social class may partly account for the differences.…”
Section: Discussioncontrasting
confidence: 69%
“…The 17.8% rate of reported suicidal thinking during a monthly period found in this sample of elderly aboriginal women might be considered relatively high. Compared to a study of non-aboriginal elderly women in Taiwan, which found a 13.5% one-month prevalence rate of suicidal thinking (Chen et al, 2007), our results show elderly aboriginal women report a higher frequency of suicidal ideation. Lower social class may partly account for the differences.…”
Section: Discussioncontrasting
confidence: 69%
“…1e3 Depression and hypnotics use were, in particular, suggested as strong correlates with poor sleep. 4,5 Conversely, various alterations of sleep architecture (e.g., decreased deep sleep, impaired sleep continuity, and duration) can be identified in patients with depression. 6 The relationship between depression and sleep disturbance has been hypothesized to be bidirectional, with depression increasing the risk of poor sleep and poor sleep predicting depression.…”
Section: Introductionmentioning
confidence: 98%
“…6 The relationship between depression and sleep disturbance has been hypothesized to be bidirectional, with depression increasing the risk of poor sleep and poor sleep predicting depression. 3,6,7 While late-life depression in the community was prevalent, ranging from 8.8%e15.3%, 4,8 severe depressive disorder was found in less than 3% of these people. 9 Different manifestations of late-life depression that might be distinctive from major depression 4 are likely to be one of the explanations causing variations in prevalence.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…There is less information on late life depression internationally but certainly it is recognized as common and as a major public health problem at least in the United States (Steffens et al ., 2006) across ethnic groups (Blazer, 2003), in Europe (Copeland et al ., 2004) and in other countries. (Papadopoulos et al ., 2005; Chen et al ., 2007) Low estimates of depression in the Chinese population have been reported. (Zhang et al ., 1998; Demyttenaere et al ., 2004) However, little is known on late life depression in the rural elderly Chinese population which accounts for three quarters of the country’s elderly population.…”
Section: Introductionmentioning
confidence: 99%